2013
DOI: 10.1002/jcop.21566
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Support Group Communication for Women With Postpartum Depression: How Support Groups Silence and Encourage Voices of Motherhood

Abstract: This phenomenological study sought to determine how social support communication compares between types of support groups for women with postpartum depression (PPD). Participants were 27 women who had given birth. Participants attended one of three types of support groups: a PPD support group, a local mothers’ group, or a working moms’ group. Findings indicate that there are differences in the way social support functions between these groups; however, all participants indicated attending group support as a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Support groups have been proven to be effective in addressing distress in people with chronic conditions (Cutler, 2018) and for caregivers of people with dementia (Dam et al, 2016). They have also been used to provide social support to mothers with postpartum depression (Anderson, 2013) and have been shown to improve social outcomes in stroke patients (White, 2016). Support groups have also been linked to long-term effectiveness for the caregivers of people with mental illnesses (Worrall et al, 2018) and have been found to be a great source of social support, a safe space to address shared experiences, and a way to improve social isolation (Kirst-Ashman & Hull, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Support groups have been proven to be effective in addressing distress in people with chronic conditions (Cutler, 2018) and for caregivers of people with dementia (Dam et al, 2016). They have also been used to provide social support to mothers with postpartum depression (Anderson, 2013) and have been shown to improve social outcomes in stroke patients (White, 2016). Support groups have also been linked to long-term effectiveness for the caregivers of people with mental illnesses (Worrall et al, 2018) and have been found to be a great source of social support, a safe space to address shared experiences, and a way to improve social isolation (Kirst-Ashman & Hull, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…First, a healthcare provider might educate key members of a mother’s social support network on the importance of social support in the postpartum period, and encourage the provision of proactive support. In addition, mothers might be encouraged to join peer groups, which are commonly available in the community in both an in-person format (such as a class available at a local clinic or community center) or a virtual format (such as over a social media platform) as these have shown to be effective sources of support [ 69 ]. Additionally, for mothers who lack material and financial supports, healthcare providers could work to help connect postpartum mothers to existing social service resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, uptake has been poor and research suggests that this may be due, in part, to the stigmatization of women whose experiences of pregnancy and motherhood do not align with idealized societal norms. For example, scholarship on postpartum depression suggests that women are discouraged from disclosing symptoms and seeking help for fear of being judged as bad mothers (Anderson 2013; Beck 2002). Other research demonstrates how the discourse of the ‘good mother’ as a ‘happy mother’ contributes to antenatal anxiety and depression (Staneva & Wigginton 2018), and how social expectations of pregnancy engender and exacerbate antenatal distress (Staneva et al .…”
Section: Introductionmentioning
confidence: 99%